A kernel regression approach for identification of first order differential equations based on functional data. (May 2022) - Li, X.Y.; Wu, B.Y.
Abstract: Differential equations models for functional data play a strong role in economics, medicine, and so on. It is challenging to identify a linear differential operator from functional data. The purpose of this letter is to find a new identification approach for differential equations models based on functional data. The effectiveness of our approaches are verified through numerical experiments.